Penerapan Bahan Manipulatif Balok Garis Dapat Meningkatkan Pembelajaran Operasi Hitung Campuran Bilangan Bulat - Siti Sovia Aprilia; H. U. Abdul Azis; Muhammad Arif (Indonesian Journal of Integrated Science and Learning, 2023)
This research aims to obtain data on the application of line beam manipulative materials to improve learning of mixed whole number arithmetic operations at Class VI Neglasari State Elementary School. This research was carried out at Neglasari State Elementary School in class VI consisting of 30 students. Data collection techniques were carried out using observation and final tests. Data analysis was carried out descriptively. The research results showed that the percentage of student completion increased from 60% in cycle 1 learning activities to 93.3% in cycle 2 learning activities. Only 6.6% of students had not reached the Kkm score, with a class average score of 74.33. According to these data, it can be concluded that the use of manipulative materials can improve students' learning outcomes and activities in the Mathematics subject regarding mixed whole number arithmetic operations in class VI of Neglasari State Elementary School.